Taguchi design of experiments based optimization and experimental investigation of mechanical performance of hybrid epoxy nanocomposites - Upadhyay Avani Kumar; Ajay Kumar; Rashi Nathawat (Zaštita Materijala)
The rising demand of safety in the aerospace and automobile industry is continuously motivating researchers to develop high strength, lightweight hybrid polymer composites, usually consisting a combination of carbon nanotubes (CNTs) and ceramic nanoparticles in the epoxy matrix. However, the development of such composites are usually hindered by some existing challenges, such as optimization of the concentration of CNTs, nanoparticles and their distribution in viscous epoxy matrices. In order to make the most of the impressive mechanical characteristics of CNTs and SiO2 nanoparticles, ultrasonic dual mixing (UDM) technique was employed to develop MWCNT/SiO2 based hybrid epoxy nanocomposites (HENCs). A well-known approach, such as the Taguchi design of experiment, was used to optimize the concentration of MWCNT, SiO2 nanoparticles in epoxy and curing cycle of epoxy with respect to the tensile strength of the resulting HENCs. Additionally, the tensile strength, Young's Modulus, Strain to failure, and hardness were measured for HENCs. The results revealed that the optimal concentration of 1% MWCNT and 10% SiO2 leads to the maximum increase in tensile strength and other mechanical properties of the HENCs.